2021
DOI: 10.1108/ijm-04-2020-0171
|View full text |Cite
|
Sign up to set email alerts
|

Green HRM promotes higher education sustainability: a mediated-moderated analysis

Abstract: PurposeIn the contemporary world, where sustainability at higher education is at the forefront, the ever-changing business ecosystem nurtures a new drift towards economic, environmental and social performance. This study aims to measure the impact of green human resource management (GHRM) practices on sustainability in the higher education of a developing country context through a theoretical aspect of Resource-Based View (RBV).Design/methodology/approachThis study adopted a quantitative approach to propose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 59 publications
1
11
1
2
Order By: Relevance
“…This is also in line with recent research (e.g. Aboramadan et al, 2021b;Abbas et al, 2022;Kambur and Akar, 2022;N 5 48, 38, 33;Items 5 26, 16, 30, respectively). The results of EFA revealed that all items of ESEL loaded on one factor, and their factor loadings exceeded 0.55.…”
Section: Content Expert Validation and Exploratory Factor Analysissupporting
confidence: 93%
“…This is also in line with recent research (e.g. Aboramadan et al, 2021b;Abbas et al, 2022;Kambur and Akar, 2022;N 5 48, 38, 33;Items 5 26, 16, 30, respectively). The results of EFA revealed that all items of ESEL loaded on one factor, and their factor loadings exceeded 0.55.…”
Section: Content Expert Validation and Exploratory Factor Analysissupporting
confidence: 93%
“…Before data collection, we conducted a statistical power analysis to establish the minimal sample size necessary to estimate the proposed model. Assuming an anticipated effect size of 0.150, a desired statistical power of 80%, five predictors and a confidence level of 0.95, the minimum needed sample size to estimate the model was 91 (Abbas et al, 2021;Green, 1991). Our sample sizes were 150 for the UAE and 155 for Canada, sufficient to estimate the proposed model.…”
Section: Employees' Passion and Work-related Outcomesmentioning
confidence: 99%
“…RBV encourages the use of internal resources to improve performance, both tangible and intangible resources (Collis, 1994;Abbas et al, 2021). Those resources allow a company to create products that are more valuable compared to those of competitors (Barney, 2001;Kryscynski et al, 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…RBV encourages the use of internal resources to improve performance, both tangible and intangible resources (Collis, 1994; Abbas et al. , 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%